A Mechanistic Model for the Organization of Microtubule Asters by Motor and Non-Motor Proteins in a Mammalian Mitotic Extract - Chakravarty, Arijit (The American Society for Cell Biology, 2004)
We used computer simulation to understand the functional relationships between motor (dynein, HSET, and Eg5) and non-motor (NuMA) proteins involved in microtubule aster organization. The simulation accurately predicted microtubule organization under all combinations of motor and non-motor proteins, provided that microtubule cross-links at minus-ends were dynamic, and dynein and HSET were restricted to cross-linking microtubules in parallel orientation only. A mechanistic model was derived from these data in which a combination of two aggregate properties, Net Minus-end–directed Force and microtubule Cross-linking Orientation Bias, determine microtubule organization. This model uses motor and non-motor proteins, accounts for motor antagonism, and predicts that alterations in microtubule Cross-linking Orientation Bias should compensate for imbalances in motor force during microtubule aster formation. We tested this prediction in the mammalian mitotic extract and, consistent with the model, found that increasing the contribution of microtubule cross-linking by NuMA compensated for the loss of Eg5 motor activity. Thus, this model proposes a precise mechanism of action of each noncentrosomal protein during microtubule aster organization and suggests that microtubule organization in spindles involves both motile forces from motors and static forces from non-motor cross-linking proteins.